The 1897 Greko-Ottoman war - Yılmaz, Mehmet Oytun. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2003., 2003)
The 1897 Greko-Ottoman War took place in the last decade of the Nineteenth Century where the societal transformation of the Ottoman Society had already produced a powerful public opinion. The Ottoman Statesmen were perfectly aware that in the modern world government meant the consent of the public. They employed different tactics from time to time to get this consent and reinforce their legitimacy. A modern war constitutes a platform on whichthe above relation between the state and the public opinion could be observed. The state is in a practical need of man-power and the need for public consent is at maximum . The war sheds light on the tactics and maneuvres the state employs and as well on the reactions of the society. This thesis aims to analyse the efforts of the Ottoman State to appeal to its multi-national and multi-religious society during the 1897 war. What ever the causes may be, the Ottoman Society was to a great extent mobilized during the war. Voluntary action to go to war, aid commissions to finance the military or the extensive amount of charity activities are the evidence for this mobilization. On the other hand the war was fought with Greece who claimed to counter- mobilize a large sum of Orthodox Ottoman subjects. The Ottomans had to deal with a public which involved a huge fifth column in a nationalistic perspective. The expectation of the Greek Statesmen was that the "Rum" component would rebel and join the Greek army. The loyalty of thousands of "Rums" reinforced the victory of the Ottoman Ideology aiming to embrace rather than discriminate them.
Keywords: Greco-Turkish War, 1897.